10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background/Local Problem:Oncology providers are regularly exposed to grief, contributing to rising rates of burnout in practicing oncologists and trainees. Improved supportive interventions to combat grief are necessary. One solution is utilization of palliative care expertise to facilitate debriefing sessions, which provide protected time and space to discuss emotions related to oncology practice. Methods/interventions This pilot study aimed to evaluate how debriefing sessions led by a palliative care physician helped fellows cope with burnout and grief. Fellows at a large academic hematology/oncology program attended four debriefing sessions and completed a survey after each session. Descriptive statistics were utilized to analyze survey responses. Results A total of 43 surveys were completed. Thirty-six respondents (83.7%) endorsed experiencing professional grief in the past 6 months; 20 respondents (46.5%) endorsed experiencing personal grief. Thirty-eight respondents (88.4%) reported that debriefing sessions provided time and space to discuss grief, with 79.1% indicating benefit after the first session. All respondents reported the desire for debriefing sessions to continue. Conclusions Debriefing is an inexpensive solution to the problem of increasing grief and burnout in oncology trainees. These findings suggest the importance of adopting similar palliative care-led practices throughout fellowship training programs and at other levels.